Our Neighbours, Ourselves : Contemporary Reflections on Survival. - Bhabha, Homi K. (Hegel Lectures, 2011)
The highlight of the Dahlem Humanities Center's public activities at the Freie Universität Berlin is the annual Hegel Lecture. Addressing a broader public, it has become one of the most visible events in the German capital. The lecture is indebted to the central value of the philosophy of the personality remembered in its title: freedom.